2016
DOI: 10.1002/adom.201600270
|View full text |Cite
|
Sign up to set email alerts
|

Powerful and Tunable THz Emitters Based on the Fe/Pt Magnetic Heterostructure

Abstract: Terahertz (THz) wave, which lies in the frequency gap between infrared and microwave, has an electromagnetic spectrum conventionally defined in the range from 0.1 to 30 THz. [1][2][3] Because its corresponding photon energy has a scale of milli-electron volt (meV) coinciding with the energy scale of many collective excitations in materials, [1] it has a great potential in fundamental scientific research, [4][5][6][7] THz imaging [8,9] and security applications [3] . Driven by these scientific and technological… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
189
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(207 citation statements)
references
References 37 publications
6
189
3
3
Order By: Relevance
“…This can be attributed to the magnetic shape anisotropy induced by demagnetitzation parameter of the subwavelength stripe structure . As previous work demonstrated, the THz amplitude has a strong proportional correlation with the magnetic moment . However, in sharp contrast, the maximum peak‐to‐peak values of THz signal are obtained at θ = 0°, 180°, and 360°, at which the magnitudes of M @2000 Oe are minimum.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…This can be attributed to the magnetic shape anisotropy induced by demagnetitzation parameter of the subwavelength stripe structure . As previous work demonstrated, the THz amplitude has a strong proportional correlation with the magnetic moment . However, in sharp contrast, the maximum peak‐to‐peak values of THz signal are obtained at θ = 0°, 180°, and 360°, at which the magnitudes of M @2000 Oe are minimum.…”
mentioning
confidence: 83%
“…It has been well known that metamaterial can be used to effectively control the THz wave propagation, even as a broadband THz source . By structuring a spintronic THz source in a grating type, Yang et al observed a modification of the emitted THz waveform as the THz emitter is rotated about the surface normal . However, the role of microstructure on the actual magnetization and on the absorption of pump pulses of the spintronic THz emitter remains unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…14 Recently, THz sources based on metallic spintronic heterostructures were shown to be a n e w a n d p r o m i s i n g c l a s s o f T H z emitters. 15,16,17,18,19,20,21 When excited with 10 fs nanojoule-class laser pulses from an oscillator, a gapless spectrum from 1 to 30 THz and a conversion efficiency comparable to or even better than standard oscillator-based THz emitters were achieved. 22 Advantages of this emitter concept are ease-of-use, stability and a collinear geometry.…”
mentioning
confidence: 99%